ANALISIS DETERMINASI SPIRITUALITAS TERHADAP SUBJECTIVE WELL-BEING NARAPIDANA LAKI-LAKI DI LEMBAGA PEMASYARAKATAN KELAS II A BANYUWANGI - Sulthon Baihaqi, Ahmad; Mahmudah, Mahmudah; Wiarsih, Nur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The aim of the research is to determine the value of determination between Spirituality and Subjective Well-Being of prisoners at the Class II A Banyuwangi Penitentiary. The method used uses a quantitative approach, while the type of research uses descriptive research. The population is male inmates at class II A prison in Banyuwangi, for the sample using a simple random sampling method, samples taken only from male Islamic inmates who received spiritual guidance. To collect data using observation methods, questionnaires, and documentation. Data analysis uses a simple linear regression method. The results of the research show that there is a significant influence between spirituality on the subjective well-being of male inmates of class II A Banyuwangi community institutions, with a correlation value of r = 0.618 which has a strong positive linear relationship, meaning that the higher the level of spirituality of the inmates, the more it will increase level of subjective well-being of prisoners. The R Square value is 0.382. This means that the effective contribution made by spirituality to subjective well-being is 38.2%, while the remaining 61.8% is influenced by other factors that cannot be explained in this research